Bunny vs. Monkey - Smart, Jamie (Scholastic Inc., 2016)
When mean, selfish Monkey is sent into space, his spaceship crash-lands in Bunny's peaceful forest home, and Monkey, believing he is on a new planet, tries to claim it for his own.